Irradiation Experiment for Living Insect-Based Radiological Dispersal Device - Braden Goddard; Walid Metwally; Ahmad Ababneh (International Journal of Nuclear Security, 2018)
People generally associate fear with “nuclear”, “radioactive” and “insects”. It is speculated that a release of radioactive living insects would instill more fear into the general public than a “traditional” style radiological dispersion device (RDD). This paper evaluates the potential threat of an insect-based RDD using experimental data. The results of this project found that insect-based RDDs are an insignificant threat due to the challenges in making insects radioactive enough to pose any danger to humans without killing the insects.
Keywords: Neutron activation; nuclear security; radiological dispersion device; insect